ANALISIS BAKTERI SIMBION MANGROVE AVICENNIA MARINA SEBAGAI ANTIFOULING - Alifia Rizky Novitasari; Nor Sa'adah; Mahmiah (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2021)
The accumulation of biofouling on a substrate causes material loss and huge economics in the maintenance of aquaculture systems, ship hulls, seawater pipelines, coastal power plants, and other marine infrastructure. Prevention of the attachment of biofouling organisms using antifouling paints that have been developed and used for a long time. Antifouling paint contains chemical compounds (biocides). The most sensitive organisms to antifouling paint are gastropods and bivalve that cause endocrine disorders, larval disorders and shell malformations. This study aims to obtain antifouling bacteria through the isolation process of bacteria obtained from the bark Avicennia marina mangrove. The method was beginning with isolation of bacteria bark of Avicennia marina mangrove, identification of bacteria, and antifouling activity test. The results obtained from isolation of bacteria, there are 9 bacteria endophytic symbionts of the inner bark and 9 epiphytic bacteria of the outer bark. The inhibition zone test of the endophytic bacteria in the bark showed that there was no antifouling activity.